(untitled) (Nigerian Journal of Pharmaceutical Research, 2021)
Background: Spondias mombin L. belongs to the family Anacardiaceae. Despite its wide ethnomedicinal applications in the management of diverse diseases, there is a paucity of documented reports on its standardization. Objectives: The present study evaluated microscopical characters and some physicochemical properties of different parts of the plant for its identification and standardization. Material and Methods: Epidermal tissue preparation of the leaf of Spondias mombin (SM) was obtained using physical method while thin sections (10-12 μm) of the stem bark and root were obtained using a rotary microtome. Physicochemical parameters were determined for the powdered samples of SM using standard methods. Results: Diagnostic characters from the epidermal tissue of the leaf revealed anomocytic, paracytic stomatal type, non-glandular trichome, smooth to slightly wavy anticlinal walls while sections of the stem bark and root were characterized with abundant sclereids and calcium oxalate crystals. The stomatal number and stomatal index of the abaxial epidermis were 23.70±0.86 and 24.62±0.78 %, respectively. Ethanol had the highest extractive value (17.84±0.50) % in the leaf whereas it was lowest in petroleum ether (1.92±0.08) %. The leaf had the lowest ash value (7.13±0.76) %. Conclusion: The microscopical characterization and some of the physicochemical parameters reported herein could be useful in the compilation of monograph for the correct identification of Spondias mombin, thus contributing to the knowledge of its collection and preservation